PENGARUH MODEL PEMBELAJARAN BRAINWRITING TERHADAP KETERAMPILAN MENULIS MAHASISWA - Restio Sidebang; Rita Herlina Br PA (Universitas Quality, 2023)
This study aims to determine the influence of the Brain Writing learning model on the ability to write articles for semester 2 students of Quality University for the 2022/2023 academic year. This type of research uses quantitative methods that refer to a type of quasi-experimental research approach with a one-group pretest-posttest design method.The research subjects were 21 students. The research instrument for data collection is by essay test in the form of assignments, namely writing articles. Based on the research method, the research data is distinguished between before and after treatment using the Brainwiting model.The results of the data with the Shapiro Wilk test produced normally distributed data, homogeneous and non-homogeneous data, so that then a non-parametric test (Wilcoxon test) was used, the result of the significance t test of 0.00 was smaller than 0.005.There is a difference in the average results of student pretests before using the Brainwriting learning model and the average positive postest score, so it means that experimental class scores are better by using the Brainwriting learning model.The conclusion in this study is that the Brainwriting Learning Model affects the ability to write student articles.